2022
DOI: 10.1371/journal.pntd.0010811
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics coupled with in vitro model to study the early crosstalk occurring between newly excysted juveniles of Fasciola hepatica and host intestinal cells

Abstract: Fasciolosis caused by the trematode Fasciola hepatica is a zoonotic neglected disease affecting animals and humans worldwide. Infection occurs upon ingestion of aquatic plants or water contaminated with metacercariae. These release the newly excysted juveniles (FhNEJ) in the host duodenum, where they establish contact with the epithelium and cross the intestinal barrier to reach the peritoneum within 2–3 h after infection. Juveniles crawl up the peritoneum towards the liver, and migrate through the hepatic tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 83 publications
(95 reference statements)
2
2
0
Order By: Relevance
“…More specifically, we identify FhCL3 and FhCB3 as potential PLG-binding proteins, and FhCL1, FhCL2 and FhCB2 to a lesser extent. This is consistent with the developmental stage-specific expression of these proteases, being FhCB1-3 and FhCL3 mostly expressed in the juvenile stages of the parasite that are found in the duodenum [ 36 , 48 , 49 ]. However, one of the limitations of our 2D-MS approach is that it is performed under denaturing conditions, which may expose internal PLG-binding epitopes in some proteins that are not employed for PLG-binding in a real physiological context.…”
Section: Discussionsupporting
confidence: 83%
“…More specifically, we identify FhCL3 and FhCB3 as potential PLG-binding proteins, and FhCL1, FhCL2 and FhCB2 to a lesser extent. This is consistent with the developmental stage-specific expression of these proteases, being FhCB1-3 and FhCL3 mostly expressed in the juvenile stages of the parasite that are found in the duodenum [ 36 , 48 , 49 ]. However, one of the limitations of our 2D-MS approach is that it is performed under denaturing conditions, which may expose internal PLG-binding epitopes in some proteins that are not employed for PLG-binding in a real physiological context.…”
Section: Discussionsupporting
confidence: 83%
“…More specifically, we identify FhCL3 and FhCB3 as potential PLG-binding proteins, and FhCL1, FhCL2 and FhCB3 to a lesser extent. This is consistent with the developmental stage-specific expression of these proteases, being FhCB1-3 and FhCL3 mostly expressed in the juvenile stages of the parasite that are found in the duodenum (46)(47)(48). However, one of the limitations of our 2D-MS approach is that it is performed under denaturing conditions, which may expose internal PLG-binding epitopes in some proteins that are not employed for PLG-binding in a real physiological context.…”
Section: Discussionsupporting
confidence: 80%
“…Such analysis could however be particularly useful in revealing novel facets of the pathological mechanisms associated with human strongyloidiasis, especially when applied in comparative studies. Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
“…Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70]. Importantly, a number of studies identified parasite proteins within the host's systemic or vesicular proteome, supporting the relevance of host proteomics also in revealing novel diagnostic markers [67,68,71,72,74,75].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%